Varanus salvator (Common Water Monitor Lizard). Diet - SHREYA, BHATTACHARYA; Indraneil, Das (Society for the Study of Amphibians and Reptiles, 2025)
Varanus salvator is a large varanid, with a distribution from the Indian Subcontinent to mainland and the western portion of insular Southeast Asia. It is a dietary generalist and an opportunistic predator, known to feed on a diverse range of prey including crabs and other invertebrates, fish, frogs, turtles, snakes, birds, small to mid-sized mammals, the eggs of reptiles and birds, as well as scavenge on animal carcasses and human- generated garbage. Here, we report on a novel frog in the diet of V. salvator from East Malaysia (North- western Borneo).